Hadith #4276 - Sunan Abi Dawud - Hilal bin Yasaf هلال بن يساف; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id bin Zayd (Sunan Abi Dawud)
This is his recompense. If Allah wishes to disregard him, He may do do.
Grade: Da'if

Hadith #4646 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abdullah bin Zalm عبد الله بن ظالم التميمي المازني; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Hilal bin Yasaf هلال بن يساف; Husayn bin 'Abdur Rahman al-Salmi حصين بن عبد الرحمن السلمي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Sa'id bin Zayd; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) said: The Caliphate of Prophecy will last thirty years; then Allah will give the Kingdom of His Kingdom to anyone He wills. Sa’id told that Safinah said to him: Calculate Abu Bakr’s caliphate as two years, ‘Umar’s as ten, ‘Uthman’s as twelve and ‘Ali so and so. Sa’id said: I said to Safinah: They conceive that ‘Ali was not a caliph. He replied: The buttocks of Marwan told a lie.
Grade: Hasan Sahih

Hadith #4956 - Sunan Abi Dawud - Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Hilal bin Yasaf هلال بن يساف; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Samra bin Jundub; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
The Prophet (ﷺ) asked: What is your name? He replied: Hazn (rugged). He said: You are Sahl (smooth). He said: No, smooth is trodden upon and disgraced. Sa’id said: I then thought that ruggedness would remain among us after it. AbuDawud said: The Prophet (ﷺ) changed the names al-‘As, Aziz, Atalah, Shaytan, al-Hakam, Ghurab, Hubab, and Shihab and called him Hisham. He changed the name Harb (war) and called him Silm (peace). He changed the name al-Munba’ith (one who lies) and called him a
Grade: Sahih

Hadith #5029 - Sunan Abi Dawud - Hilal bin Yasaf هلال بن يساف; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Uthman bin Muhammad (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) sneezed, he placed his hand or a garment on his mouth, and lessened the noise. The transmitter Yahya is doubtful about the exact words khafada or ghadda (lessened).
Grade: Hasan Sahih

Hadith #5030 - Sunan Abi Dawud - Hilal bin Yasaf هلال بن يساف; Ishaq bin Yusuf bin Mrdas إسحاق بن يوسف بن مرداس; Ja'far bin Iyas; Khalid bin Arfjh خالد بن عرفجة; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Saalm bin 'Ubaid al-Ashja'i (Sunan Abi Dawud)
There are five qualities which a Muslim should display to his brother : return of salutation, response to the one who sneezes, acceptance of the invitation, paying sick visit to a patient, and accompanying the funeral.
Grade: Sahih

Hadith #5164 - Sunan Abi Dawud - Fadayl bin 'Iyyad bin Mas'ud فضيل بن عياض بن مسعود; Hilal bin Yasaf هلال بن يساف; Husayn bin 'Abdur Rahman al-Salmi حصين بن عبد الرحمن السلمي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل (Sunan Abi Dawud)
A man came to the Prophet (ﷺ) and asked: Messenger of Allah! how often shall I forgive a servant? He gave no reply, so the man repeated what he had said, but he still kept silence. When he asked a third time, he replied: Forgive him seventy times daily.
Grade: Sahih